THE Pengaruh Inflasi, Suku Bunga, Nilai Tukar, Indeks Persepsi Korupsi, dan Keterbukaan Perdagangan terhadap Investasi Asing Langsung di 6 Negara ASEAN - Fiona Fiona; Nasar Buntu Laulita (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Every country faced economic instability during the COVID-19 pandemic. Despite the economic instability, some discovered that the number of foreign direct investment inflows increases in most of ASEAN countries. This phenomenon makes investors hard to predict the level of foreign direct investment within the region. The purpose of this research is to understand which are the variables that may have impact on the inflows of foreign direct investment, specifically in ASEAN countries. Therefore, the research is conducted in 6 ASEAN countries that contribute the most to the overall foreign direct inflows in ASEAN from the year 2002 to 2021. This research uses a quantitative approach with panel data regression analysis. This research is tested in both Eviews 12. The result shows that inflation and interest rates don't affect foreign direct investment inflows significantly in the 6 ASEAN countries, whereas exchange rate, corruption perception index, and trade openness have a significant effect on foreign direct investment.